Transcription factor E2F8 is a therapeutic target in the basal-like subtype of breast cancer - Zheng, Jing; Huang, Jingyi; Xia, Jinquan; Zhou, Wenbin; Dai, Lingyun; Lin, Sihang; Gao, Lin; Zou, Chang (Frontiers in Oncology, 2023)
Tumorigenesis in breast cancers usually accompanied by the dysregulation of transcription factors (TFs). Abnormal amplification of TFs leads aberrant expression of its downstream target genes, including cascade reaction of signalling pathway and the dysfunction of immune cells in breast cancer. However, breast cancers are heterogeneous disease with different subtypes that have distinguished clinical behaviours, and the identification of prognostic TFs may enable to provide diagnosis and treatment of breast cancer based on subtypes, especially in Basal-like breast cancer. In this study, we exploited some specific TFs signatures as molecular targets in four breast cancer subtypes. The next-generation RNA sequencing analyses screened high and low expression of TFs in Luminal A, Luminal B, HER2 and Basal-like subtype cancers. Kaplan-Meier plotter suggested that high expression of both E2F8 and MYBL2 in Basal-like subtype had a poor relapse-free survival (RFS). The ROC analysis demonstrated remarkable specificities and sensibilities of these TFs as diagnostic biomarkers in breast cancer. Functional enrichment results identified that apoptosis, cell cycle, and hormone ER pathway were represented the crucial regulation pathways by both E2F8 and MYBL2. Besides, we found that these patients of high expression of E2F8 responded to chemotherapy, while those patients of high expression of MYBL2 responded to endocrinotherapy. Our data also suggested that the up-regulation of E2F8 was accompanied with higher enrichments of CD4+ T cells and CD8+ T cells in breast cancers. The results showed a positive correlation between the expression of E2F8 and PD-L1/CTLA4. Taken together, our findings elucidated a prospective target in Basal-like breast cancer, providing underlying molecular biomarkers for the development of breast cancer treatment.